CIPHERTEXT DESTRUCTION IN CLOUD STORAGE - S N, Ms. Rekha; Priya M, Ms. Guru (IJRDO -Journal of Computer Science Engineering, 2016)
In cloud services, users will frequently berequired to reveal their personal sensitiveinformation which could be stored in the cloudwhich is used for different purposes. However, ina cloud storage network, the servers are easilyprone to strong attacks and also commonlyexperience software/hardware faults. As such, theprivate information could be under risk in anuntrusted environment. Given that the personalsensitive information is usually out of user’scontrol in most cloud-based services, ensuringdata security and privacy protection with respectto untrusted storage network has become aformidable challenge in research. To addressthese challenges, in this paper we propose a selfdestructionsystem, named Cloud Sky, which isable to enforce the security of user privacy overthe untrusted cloud in a controllable way. CloudSky exploits a key control mechanism based onthe attribute-based encryption (ABE) and takesadvantage of active storage networks to allow theuser to control the subjective life-cycle and theaccess control polices of the private data whoseintegrity is ensured by using HMAC to cope withuntrusted environments. The feasibility of thesystem by its performance and scalability isdemonstrated by experiments on a large-scalestorage network.